2018
DOI: 10.1016/j.cub.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese giant salamander exemplifies the hidden extinction of cryptic species

Abstract: Overexploitation, habitat destruction, human-driven climate change and disease spread are resulting in the extinction of innumerable species, with amphibians being hit harder than most other groups [1]. Few species of amphibians are widespread, and those that are often represent complexes of multiple cryptic species. This is especially true for range-restricted salamanders [2]. Here, we used the widespread and critically endangered Chinese giant salamander (Andrias davidianus) to show how genetically uninforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
115
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 83 publications
(135 citation statements)
references
References 9 publications
10
115
3
1
Order By: Relevance
“…We analyzed samples from 21 historical Chinese giant salamander museum specimens with collection locality information obtained from China before 1922, and 20 tissue samples previously analyzed by Murphy et al () and Yan, Lü, et al () obtained in 1992 from giant salamanders with reported wild localities. Available samples represent four separate river drainages and nine provinces or equivalent administrative units and include the holotypes of Andrias davidianus and Megalobatrachus sligoi (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We analyzed samples from 21 historical Chinese giant salamander museum specimens with collection locality information obtained from China before 1922, and 20 tissue samples previously analyzed by Murphy et al () and Yan, Lü, et al () obtained in 1992 from giant salamanders with reported wild localities. Available samples represent four separate river drainages and nine provinces or equivalent administrative units and include the holotypes of Andrias davidianus and Megalobatrachus sligoi (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…However, exploitation of giant salamanders increased in China from the late 1970s onwards, following the freeing of internal movement of people within China and the spread of southern Chinese migrants who had traditionally eaten the species; this led to trade and movement of animals across the country to supply a domestic luxury food market, and to development of a massive‐scale farming industry which has grown rapidly and expanded from southern Shaanxi Province across China since the early 2000s (Cunningham et al, ). The farming industry poses a huge threat to wild populations through continuing illegal harvesting of wild animals to stock farms, and serious risk of infectious disease transmission and genetic pollution associated with accidental escapes or deliberate “conservation” releases of farmed animals that have been moved around the country (Cunningham et al, ; Turvey et al, ; Yan, Lü, et al, ). The Chinese giant salamander is now listed as Critically Endangered by IUCN () and is recognized as a global conservation priority for maintaining evolutionary history (Isaac, Redding, Meredith, & Safi, ), because there are only two other living cryptobranchids (Japanese giant salamander, Andrias japonicus ; hellbender, Cryptobranchus alleganiensis ), which are both listed as Near Threatened by IUCN ().…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations